2019
DOI: 10.2478/pjg-2019-0004
|View full text |Cite
|
Sign up to set email alerts
|

Porosity Distribution and Differentiation of Different Types of Fluids in Reservoir of Sawan Gas Field, Lower Indus Basin, Pakistan

Abstract: The lower Indus basin is one of the prolific basins in Pakistan in which the C-interval of lower Goru formation act as a reservoir. With the help of petrophysical interpretation production zone is recognized and also porosity is calculated at the reservoir level. Through porosity we are able to calculate Ksat. A model based inversion of 2D seismic inversion was performed to ascertain three dimensional dispersion of acoustic impedance in the investigation zone and we have recognized new areas where porosity dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Although complex and nonlinear relationship exists between the thinly layered media and seismic waveforms, SVM established nonlinear projection relationship to capture the thinly layered media from the seismic waveform. In contrast, the inverted AI from model-based or other traditional algorithms applied previously in the same dataset have not been good enough to capture the small lithological variations [18,19]. What is more, overall lateral and vertical variations in the resolution of AI estimated from traditional inversion algorithms was poor and resulted in discontinuity of seismic event.…”
Section: Reservoir Characterization From Seismic Datamentioning
confidence: 91%
See 1 more Smart Citation
“…Although complex and nonlinear relationship exists between the thinly layered media and seismic waveforms, SVM established nonlinear projection relationship to capture the thinly layered media from the seismic waveform. In contrast, the inverted AI from model-based or other traditional algorithms applied previously in the same dataset have not been good enough to capture the small lithological variations [18,19]. What is more, overall lateral and vertical variations in the resolution of AI estimated from traditional inversion algorithms was poor and resulted in discontinuity of seismic event.…”
Section: Reservoir Characterization From Seismic Datamentioning
confidence: 91%
“…In the past few years, multiple studies have been carried out to evaluate the remaining potential of the C-sand interval using modern techniques [15][16][17]. Recent studies performed by Ali et al [18] and Asad and Rahim [19] indicated that model-based post-stack inversion presented good results for the spatial distribution of reservoir properties and mapping potential gas-saturated zones in the C-sand interval. Even though the model-based inversion algorithm achieved good results, the quantification of the highly productive area was scaled relative to the whole body of the reservoir.…”
Section: Introductionmentioning
confidence: 99%